Building an integrated healthcare system of China: an assessment of coupling coordination between disease prevention, medical services, and healthcare financing from 2012 to 2021 - Guowu Huang; Wanying Wu; Qiaoxi Wen; Liyong Lu; Jay Pan (Health Economics Review)
Abstract Background Universal Health Coverage (UHC) is a central component of the Sustainable Development Goals, and integrated healthcare is recognized as a key pathway to achieving UHC. China’s healthcare reform, aimed at realizing the “Healthy China 2035” goal, faces challenges in ensuring the coordinated development of disease prevention, medical services, and healthcare financing. However, empirical research assessing the integration of these three systems in China is scarce. Purpose This study aims to assess the coupling and coordination between disease prevention, medical services, and healthcare financing in China from 2012 to 2021, with the goal of providing a comprehensive evaluation of the progress made in building an integrated healthcare system. Methods The study employs the Entropy Weight Method (EWM) to determine the weight of each system index, followed by the Coupling Coordination Degree Model (CCDM) to measure the coordination among the three components. The Grey Correlation Analysis (GCA) is used to identify key driving factors, and the Grey Prediction Model (GM (1.1)) is applied to forecast future trends of integrated healthcare development across Chinese provinces. Results The coupling coordination degree of the three systems ranged from 0.12 to 0.73 from 2012 to 2021, reflecting a shift from moderate imbalance to mild imbalance over time. Regional disparities were observed, with eastern provinces showing higher levels of integration than western provinces. The disease prevention subsystem emerged as the primary constraint to the overall integration process. Most regions exhibited a consistent upward trend in the coupling coordination index, though development speeds varied significantly across provinces. Conclusion While China’s integrated healthcare system has shown progress, there is still considerable room for improvement. Strengthening disease prevention efforts is critical to enhancing the overall coordination of the healthcare system. This study provides valuable insights for other developing countries facing similar challenges in healthcare integration.